Partisipasi Masyarakat dalam Musyawarah Pembangunan Desa (MUSREMBANGDES) di Desa Meranti Kecamatan Tapa Kabupaten Bone Bolango - Regita G. Alulu; Irawaty Igirisa; Fenti Prihatini (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
Village Development Planning Deliberation (Musyawarah Perencanaan Pembangunan Desa or Musrenbangdes) is a participatory forum designed to accommodate community aspirations in village development planning. This study aims to analyze community participation in the Musrenbangdes process in Meranti Village, Tapa District, Bone Bolango Regency, covering the stages of decision-making, implementation, benefit utilization, and activity evaluation. The study employed a qualitative approach focusing on community involvement throughout each stage of Musrenbangdes. The findings reveal that community participation remains suboptimal. In the decision-making stage, village officials continue to dominate the process, resulting in limited community influence on final decisions. During the implementation stage, community attendance at forum meetings is relatively low due to work-related commitments, although participation in physical development activities through mutual cooperation remains high. In the benefit utilization stage, the community has experienced the advantages of infrastructure development; however, the distribution of these benefits is still uneven, and community involvement in determining development priorities remains limited. Meanwhile, the evaluation stage is identified as the weakest aspect, as evaluations are primarily conducted internally by village officials without formally involving community members. These findings indicate that community participation in Musrenbangdes is still largely consultative and symbolic, highlighting the need for greater efforts to promote more active and meaningful community involvement throughout all stages of village development.